Analisis Pengendalian Kualitas Produk Menggunakan Metode Statistical Process Control pada Konveksi Dimas Bag Collection di Grobogan - Laila Nur Waqidah; Sunarso (Teewan Journal Solutions, 2026)
This study aims to analyse the implementation of production quality control at Konveksi Dimas Bag Collection in Grobogan. Adopting a case study research design with a survey method, this study specifically examines the effectiveness of product quality control using the Statistical Process Control (SPC) method. The analysis process includes determining quality standards, comparing them with production results, and evaluating defective products using SPC control tools to generate recommendations for improvement. The results indicate that the quality control process at Konveksi Dimas Bag Collection is not yet fully under control. This is statistically proven through a control chart that shows four data points outside the Upper Control Limit (UCL) and Lower Control Limit (LCL), namely in January (0.250), March (0.336), June (0.339), and August (0.303). This finding confirms the first hypothesis (H1) that quality control has not been implemented properly. Furthermore, five dominant types of defects were identified: folded seams, understitching, torn fabric, loose seams, and misaligned seams. The cause-and-effect analysis shows that the factors causing damage originate from human, machine, material, and work method aspects, which also support the validity of the second hypothesis (H2).